CONTRIBUTION OF CORPORATE GOVERNANCE PRACTICES TO FINANCIAL DISTRESS FACING LOCAL AUTHORITIES IN KENYA. - Ntoiti, Dr. John; Gakure, Prof. Roselyn, W.; Waititu, Dr. Gichuhi A. (American Journal of Leadership and Governance, 2017)
Purpose: The purpose of this study was to establish the contribution of corporate governance practices to financial distress facing local authorities in Kenya. Methodology: A descriptive research design was used to conduct the study. The study population comprised of the 175 Local Authorities in Kenya. A sample of 20 Local Authorities was selected using a stratified random sampling technique. A questionnaire was used to collect data from both the Local Authorities officers and customers of Local Authorities. The data collected was analyzed using descriptive and inferential statistics. Qualitative responses were analyzed using content analysis. Results: Results indicated that Local Authorities had poor governance practices. Specifically, Local Authorities did not ensure transparency through the display of performance results to all stakeholders. In addition, the Local Authorities do not have a good leadership structure which supports corporate governance. It was also observed from the results that the number of corruption cases had not reduced in Local Authorities. Unique contribution to theory, practice and policy: The studies recommended that there should be clearly defined boundaries between political and administrative wings and minimize interference by politicians in the implementation of policies and the recruitment of bureaucrats to ensure efficiency and effectiveness. The culture of kickbacks and corruption should be eliminated through a cultural and mind set change.